Clinical and Radiological Study of Patients With Skull Base Fracture After Head Injury - Oktavian, Puguh; Romdhoni, Achmad Chusnu; Dewanti, Linda; Fauzi, Asra Al (Folia Medica Indonesiana, 2021)
Traumatic brain injury (TBI) is the largest contributor to morbidity and mortality in various parts of the world. Skull base fracture (SBF) is one of the many manifestations that can occur in cases of mild to severe TBI. With varying patterns of TBI, it was necessary to review the characteristics of SBF, clinical manifestations, cerebrospinal fluid leakage, and complications. The data were taken from the medical records of SBF patients who were treated at RSUD (Regional Public Hospital) Dr. Soetomo in the period January 2014 - July 2019. Then, the data obtained were written on the collection sheet and analyzed descriptively using RKward. It was found that SBF most often occurs due to severe TBI (60.14%). 77.7% of SBF patients were male and 35.1% of all patients aged 15-24 years. The most frequent cause was traffic accidents (86.5%). The anterior cranial fossa (ACF) was the most frequently fractured part of the skull base (30.4%). There was a significant relationship between the severity of TBI with the occurrence of CSF leakage and complications. About 33 patients (22.3%) had complications such as pneumocephalus and 9 patients (6.1%) had meningitis. Complications in the form of brain abscess and hydrocephalus in 1 (0.7%) patient each. SBF often occurred in men of productive age 15-24 years. The ACF was the most frequently fractured part. The majority were caused by traffic accidents accompanied by severe brain injuries. The most common complications were pneumocephalus, meningitis, brain abscess, and hydrocephalus.